Deficient allo‐centric visuospatial processing contributes to apraxic deficits in sub‐acute right hemisphere stroke. Issue 2 (17th June 2019) - Ubben, Simon D.; Fink, Gereon R.; Kaesberg, Stephanie; Kalbe, Elke; Kessler, Josef; Vossel, Simone; Weiss, Peter H.
Abstract : While visuospatial deficits are well‐characterized cognitive sequelae of right hemisphere (RH) stroke, apraxic deficits in RH stroke remain poorly understood. Likewise, very little is known about the association between apraxic and visuospatial deficits in RH stroke or about the putative common or differential pathophysiology underlying these deficits. Therefore, we examined the behavioural and lesion patterns of apraxic deficits (pantomime of object use and bucco‐facial imitation) and visuospatial deficits (line bisection and letter cancellation tasks) in 50 sub‐acute RH stroke patients. Using principal component analysis (PCA), we characterized the relationship between the two deficits. We hypothesized that any interaction of these neuropsychological measures may be influenced by the demands of ego‐centric/space‐based and/or allo‐centric/object‐based processing. Contralesional visuospatial deficits were common in our clinically representative patient sample, affecting more than half of RH stroke patients. Furthermore, about one‐third of all patients demonstrated apraxic deficits. PCA revealed that pantomiming and the imitation of bucco‐facial gestures loaded clearly on a first component (PCA1), while letter cancellation loaded heavily on a second component (PCA2). For line bisection, overall mean deviation loaded on PCA1, while the difference between the mean deviations in contra‐ versus ipsilesional space loaded on PCA2. These results suggest that PCA1 represents allo‐centric/object‐based processing and PCA2 ego‐centric/space‐based processing. This interpretation was corroborated by the statistical lesion analyses with the component scores. Data suggest that disturbed allo‐centric/object‐based processing contributes to apraxic pantomime and imitation deficits in (sub‐acute) RH stroke.